Nucleophosmin 1 is a prognostic marker of gastrointestinal cancer and is associated with m6A and cuproptosis - Liu, Xu-Sheng; Liu, Chao; Zeng, Jing; Zeng, Dao-Bing; Chen, Yi-Jia; Tan, Fan; Gao, Yan; Liu, Xiao-Yu; Zhang, Yu; Zhang, Yao-Hua; Pei, Zhi-Jun (Frontiers in Pharmacology, 2022)
Background: NPM1 is highly expressed in a variety of solid tumors and promotes tumor development. However, there are few comprehensive studies on NPM1 analysis in gastrointestinal cancer. Methods: We used bioinformatics tools to study the expression difference of NPM1 between gastrointestinal cancer and control group, and analyzed the relationship between its expression level and the diagnosis, prognosis, functional signaling pathway, immune infiltration, m6A and cuproptosis related genes of gastrointestinal cancer. At the same time, the expression difference of NPM1 between esophageal carcinoma (ESCA) samples and control samples was verified by in vitro experiments. Results: NPM1 was overexpressed in gastrointestinal cancer. In vitro experiments confirmed that the expression of NPM1 in ESCA samples was higher than that in normal samples. The expression of NPM1 has high accuracy in predicting the outcome of gastrointestinal cancer. The expression of NPM1 is closely related to the prognosis of multiple gastrointestinal cancers. Go and KEGG enrichment analysis showed that NPM1 co-expressed genes involved in a variety of biological functions. NPM1 expression is potentially associated with a variety of immune cell infiltration, m6A and cuproptosis related genes in gastrointestinal cancers. Conclusion: NPM1 can be used as a diagnostic and prognostic marker of gastrointestinal cancer, which is related to the immune cell infiltration and the regulation of m6A and cuproptosis.